Implementasi Strategi Active Learning Dalam Peningkatan Penguasaan Kosakata Bahasa Jerman - Misnawaty Usman; Sri Ningsi E. Maukafeli; Abdul Kasim Achmad (Phonologie : Journal of Language and Literature, 2022)
Abstract. This research was classroom action research which consisted of two cycles, each cycle consisting of planning, implementation, observation and reflection stages. The purpose of this study was to determine the increase in German vocabulary mastery of class XI students of SMA Negeri 11 Makassar through active learning strategies. The subjects of this study were students of class XI IPS 3, totaling 20 people. This research data consists of two types, namely quantitative and qualitative data. Qualitative data was obtained through observation sheets and qualitative data was obtained through tests of German vocabulary mastery in cycles I and II. The data was analyzed using the average technique. The results of this study obtained that students in the first cycle reached 74.25 and the second cycle 82 experienced an increase of 8%. This shows that the application of the active learning strategy improves the mastery of German vocabulary in class XI SMA Negeri 11 Makassar.